Prevalence of COVID-19 among patients with chronic inflammatory rheumatic diseases treated with biologic agents or small molecules: A population-based study in the first two months of COVID-19 outbreak in Italy (2020)
Objective: The aim of this study is to determine the prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease 2019 (COVID-19) among adult patients treated with biologic agents or small molecules for chronic inflammatory rheumatic diseases, in particular for chronic inflammatory arthritides. Methods: To this end, a population-based study, in the province of Udine (466,700 inhabitants, with age > 15 years old, Friuli Venezia Giulia region, Italy) was planned. The primary outcome was the prevalence of COVID-19 in the first two months of the outbreak. All the rheumatic patients treated with biologic agents or small molecules in the last 6 months in our province were included (N = 1051). Results: From February 29 toApril 25, 2020, 4 adult patients (4/1051, i.e. 3.8/1000, 95%Confidence Interval 1.5–9.7/1000) were registered as swab test positive by PCR for COVID-19. Overall, a total of 47/1051 (4.5%) cases were tested for COVID-19 by PCR in the same period, and 15 of them due to symptoms compatible with COVID-19. In the general population,the prevalence was 937 cases/466700 (2/1000, 95% Confidence Interval 1.9–2.1/1000, P-value = 0.33, chi square test), and 20,179/466,700 (4.3%) swab tests for COVID-19 were performed. Conclusion: The risk of COVID-19 in rheumatic patients under biologic agents or small molecules does not appear different from that observed in the general population. Patients should be informed to safely proceed with their treatment and follow the rules for self-protection to COVID-19.